The Effect of glycocholic acid on the growth, membrane permeability, conjugation and antibiotic susceptibility of Enterobacteriaceae - Piscon, Bar; Fichtman, Boris; Harel, Amnon; Adler, Amos; Rahav, Galia; Gal-Mor, Ohad (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionGlycocholic acid (GCA) is a steroid acid and one of the main glycine-conjugated bile components in mammalian bile, which is involved in the emulsification and absorption of fats and sterols. It is long-known that the amphipathic nature of bile acids enables them to interact with the lipid membrane of Gram-positive bacteria and act as potent antimicrobial compounds. Nevertheless, Gram-negative Enterobacteriaceae species inhabiting the intestinal tract of mammals are considered to be more bile-resistant compared to Gram-positive bacteria and are thought to tolerate high bile concentrations.ResultsHere, we show that 1-2% of GCA inhibit the growth of Enterobacteriaceae species, including E. coli, Salmonella enterica. Klebsiella spp., Citrobacter spp., and Raoultella spp. during their late logarithmic phase in liquid culture, but not in solid media. Despite their lipopolysaccharide membrane layer, we demonstrate that, in liquid, GCA increases permeability, changes the surface of the Enterobacteriaceae membrane, and compromises its integrity. These changes result in leakage of cytoplasmic proteins and enhancement of their susceptibility to antibiotics. Moreover, GCA significantly reduces bacterial motility, the frequency of bacterial conjugation and horizontal acquisition of antibiotic resistance genes. These phenotypes are associated with repression of flagellin (fliC) transcription and a sharp decrease in the occurrence of conjugative pili in the presence of glycocholic acid, respectively.DiscussionOverall, these findings broaden the current understanding about bile resistance of Gram-negative bacteria and suggest that GCA can be used to inhibit bacterial growth, augment the activity of antimicrobial compounds and diminish acquisition and dissemination of antibiotic resistance genes by conjugation.